Alkaline Treated Breadfruit (Artocarpus altilis) Based Composite Flour for the Making of Biscuit - Lubis, Yanti Meldasari; Kumalaningsih, Sri; Susanto, Tri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The objective of the research was to find out the optimum alkaline treatment to produce a light colour, starch-rich flour containing high levels of undamaged starch, intended for the making of a formulated biscuit. The research was divided into two experiments. First, a factorial randomized block design experiment with two factors: the concentration of NaOH (0.04%, 0.06%, and 0.08%) and the dipping time (15, 30 and 45 minutes). The second experiment was the use of the Linear Programming approach supported by the QSB to obtain the desirable biscuit formula. The results of the first experiment indicated that the breadfruit flour dipped for 45 minutes in the 0.08% NaOH solution was the best one. The treated flour at a moisture content of 6.63% contains 60.86% starch, 22.56% amylose, 3.25% protein, 6.26% fat, and the L value (degree of Lightness) of 74.9, water absorption index of 4.80 g/g, initiation of gelatinization temperature of 69.3 oC, gelatinization temperature of 80.9 oC, maximum viscosity of more than 2000 AU and undamaged granules. The best results of the second experiment was the biscuit formula containinq 31.76% breadfruit flour, 20% wheat flour, 13.03% red bean flour, which meets with the nutrition requirement. The texture and breaking force of the formulated biscuit was not significantly difference with the one of the biscuit made without the addition of breadfruit flour (the control), but has the lower L value. Moreover except the crispness, the colour, aroma and the taste of formulated biscuit were found the best significantly different from those of the control biscuit. Keywords: Breadfruit flour, Alkaline modification (NaOH), biscuit, Linier Programming formulation